Novel 1,2,4-Oxadiazole Derivatives in Drug Discovery - Karol Biernacki; Mateusz Daśko; Olga Ciupak; Konrad Kubiński; Janusz Rachon; Sebastian Demkowicz (Pharmaceuticals, 2020)
Five-membered 1,2,4-oxadiazole heterocyclic ring has received considerable attention because of its unique bioisosteric properties and an unusually wide spectrum of biological activities. Thus, it is a perfect framework for the novel drug development. After a century since the 1,2,4-oxadiazole have been discovered, the uncommon potential attracted medicinal chemists’ attention, leading to the discovery of a few presently accessible drugs containing 1,2,4-oxadiazole unit. It is worth noting that the interest in a 1,2,4-oxadiazoles’ biological application has been doubled in the last fifteen years. Herein, after a concise historical introduction, we present a comprehensive overview of the recent achievements in the synthesis of 1,2,4-oxadiazole-based compounds and the major advances in their biological applications in the period of the last five years as well as brief remarks on prospects for further development.